THE MEANING OF POLITICIAN BALINESE HINDU WOMENS AS SYMBOL OF SRIKANDI POLITIC IN BALI PROVINCE - Kurniasari, Ni Gusti Ayu Ketut (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2022)
This study looks at about meanings women Hindu Bali as a symbol of political a Srikandi , where in the research also linked about patrilineal culture that is in Bali province and domination patriaki system to this system political in Bali. As the basis for philosophical in this research was a Srikandi figures which is in the story of Mahabharata as one of referral basic in the teachings of Hindu believed by the majority of the community in Bali. A method of observation was used in the study directly and interview with Hindu women politicians who are in the province of Bali. As a result in this research was a heroine who had a knight brave and full of strategy is the main condition of being a female politician Hindu Bali. Patrilineal culture in effect in Bali province patriakis system and political stage in Bal, producing its own purport to female politicians Hindu Bali must have proper political strategy ability as well as the ability to communicate very flexible.